THE EFFECT OF USING WHATSAPP AS A LEARNING TOOL ON STUDENTS’ WRITING ABILITY AT MA LABORAN - Anggraini, Desti; Taridi, Muhammad; Azizah, Nur (JR-ELT (Journal of Research in English Language Teaching), 2020)
The purpose of this survey was to determine how students at MAN 1 Tanjung Jabung Barat perceive reading texts. This survey-based research is quantitative in nature. This study's participants were eleventh-grade pupils at MAN 1 Tanjung Jabung Barat. In this study, simple random sampling was used to select 50 students, or 29% of the total population, from XI IS I and XI IS II classes where 63 pupils were taught by the same teacher. In terms of data acquisition methods, a questionnaire was used. The analysis of the utilised data is a quantitative analysis. The results indicated that 80% of MAN 1 Tanjung Jabung Barat students' perceptions of reading texts fell into the category of "very good." It implies that many students at MAN 1 Tanjung Jabung Barat have positive attitudes towards reading texts.